2020
DOI: 10.1021/acsenergylett.0c01758
|View full text |Cite
|
Sign up to set email alerts
|

Broad Tunability of Carrier Effective Masses in Two-Dimensional Halide Perovskites

Abstract: The effective mass of charge carriers is a crucial parameter for the design of any optoelectronic device. The estimated values of the effective mass of 2D halide perovskites currently span a broad range, providing an unwelcome source of confusion in this promising material system. Here we highlight how the distortion imposed by the organic spacers, and orbital hybridization effects by the metal cation, govern the effective mass. As a result, the effective mass in 2D halide perovskites can be easily tailored ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
145
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(160 citation statements)
references
References 51 publications
15
145
0
Order By: Relevance
“…[ 117–121 ] For example, one very recent study reported magneto‐optical absorption measurements of n = 1−6 layered Ruddlesden–Popper perovskites, demonstrating how carrier effective masses may be tuned by varying the number of octahedral layers or swapping lead for tin at the B‐site cation. [ 122 ] Comparison of such experimentally determined masses with those derived from band structure calculations, made without consideration of polaronic effects, may further elucidate the extent to which polaronic contributions enhance carrier masses in reality.…”
Section: Experimental Approaches For Observing Polaronic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 117–121 ] For example, one very recent study reported magneto‐optical absorption measurements of n = 1−6 layered Ruddlesden–Popper perovskites, demonstrating how carrier effective masses may be tuned by varying the number of octahedral layers or swapping lead for tin at the B‐site cation. [ 122 ] Comparison of such experimentally determined masses with those derived from band structure calculations, made without consideration of polaronic effects, may further elucidate the extent to which polaronic contributions enhance carrier masses in reality.…”
Section: Experimental Approaches For Observing Polaronic Effectsmentioning
confidence: 99%
“…[ 106 ] A study of a new cadmium‐based single‐layer perovskite, (F 2 CHCH 2 NH 3 ) 2 Cd x Pb 1− x Br 4 , demonstrated the importance of structural deformation in enabling emission from self‐trapped states, with alloyed Cd‐Pb materials emitting much more strongly than either purely Cd‐ or Pb‐based materials because of increased octahedral distortions. [ 159 ] Further, swapping the organic spacer cations between BA to PEA has a significant effect on the intensity and energy of Raman modes [ 120 ] and can alter the charge‐carrier effective mass, [ 122 ] thus varying the strength of the electron–phonon interaction. This has been linked to the fact that swapping organic spacer cations modifies the stiffness or “corrugation” of the octahedral layers in Ruddlesden–Popper perovskites, aiding structural distortion and thus impacting on the likelihood of charge‐carrier localization in these materials.…”
Section: Polarons In Metal‐halide Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional insight can be obtained when considering how the diamagnetic shift and the Zeeman effect impact the luminescence. The magnitude of the exciton energy shift in the lowfield limit is given by: [7] 1/2 eff B 0 2…”
Section: Figure 6amentioning
confidence: 99%
“…[23] Finally, we point out that our set up has been used previously to measure different systems, including: GaAs/AlGaAs superlattices, [46] GaSe [47] and 2D halide perovskites. [48] To interpret our findings, we consider the behaviour of indirect band gap semiconductors in magnetic field. For an indirect band gap semiconductor such as the SnSe 2(1−x) S 2x alloy, the dependence of the band-edge absorption energy on magnetic field can be expressed as [49,50]…”
Section: Methodsmentioning
confidence: 99%